2014
DOI: 10.1093/eurheartj/ehu096
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous sodium nitrite in acute ST-elevation myocardial infarction: a randomized controlled trial (NIAMI)

Abstract: AimDespite prompt revascularization of acute myocardial infarction (AMI), substantial myocardial injury may occur, in part a consequence of ischaemia reperfusion injury (IRI). There has been considerable interest in therapies that may reduce IRI. In experimental models of AMI, sodium nitrite substantially reduces IRI. In this doubleblind randomized placebo controlled parallel-group trial, we investigated the effects of sodium nitrite administered immediately prior to reperfusion in patients with acute ST-eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 41 publications
0
94
0
1
Order By: Relevance
“…31,231,232 Intravenous nitrite in patients with ST-segment elevation myocardial infarction and interventional reperfusion failed to reduce infarct size (biomarker and MRI) or to affect TIMI flow (angiography). 233 Intracoronary nitrite in patients with ST-segment elevation myocardial infarction and interventional reperfusion reduced infarct size (creatine kinase and MRI) only in a subgroup of patients with TIMI flow ≤1 at admission, and in this subgroup, intracoronary nitrite also reduced the area of microvascular obstruction (MRI). 234 Erythropoietin in patients with STsegment elevation myocardial infarction and interventional reperfusion neither reduced infarct size (creatine kinase and MRI) nor improved TIMI flow.…”
Section: Clinical Studiesmentioning
confidence: 97%
“…31,231,232 Intravenous nitrite in patients with ST-segment elevation myocardial infarction and interventional reperfusion failed to reduce infarct size (biomarker and MRI) or to affect TIMI flow (angiography). 233 Intracoronary nitrite in patients with ST-segment elevation myocardial infarction and interventional reperfusion reduced infarct size (creatine kinase and MRI) only in a subgroup of patients with TIMI flow ≤1 at admission, and in this subgroup, intracoronary nitrite also reduced the area of microvascular obstruction (MRI). 234 Erythropoietin in patients with STsegment elevation myocardial infarction and interventional reperfusion neither reduced infarct size (creatine kinase and MRI) nor improved TIMI flow.…”
Section: Clinical Studiesmentioning
confidence: 97%
“…36 In contrast to the positive clinical studies with mechanical conditioning strategies, studies attempting to recruit cardioprotective signals pharmacologically have largely failed, including those on adenosine, [495][496][497][498] on PKCδ inhibition, 188 and on intravenous nitrite which is bio-converted to NO. 499 Erythropoietin failed to reduce IS in 2 trials, 501,502 but there was no evidence before that erythropoietin participated in the conditioning phenomena. One study on atrial natriuretic peptide demonstrated modest IS reduction, but atrial natriuretic peptide is not really an endogenous trigger or mediator of conditioning.…”
Section: Recruitment Of Cardioprotective Signaling In Patients With Amimentioning
confidence: 99%
“…Nitrite therapy is a rapidly expanding area with great potential for improved clinical outcome in patients, however caution is advised in the translation of results obtained in animal experimental models to the clinical setting. A recent multi-centre, double-blind, placebo controlled clinical trial showed that nitrite was ineffective when administered intravenously immediately prior to PPCI in patients presenting with first acute STEMI (Siddiqi et al, 2014). Therefore, we need to be mindful of differences between animal and human physiology as well as inter-individual differences in responsiveness to nitrite between subjects.…”
Section: Discussionmentioning
confidence: 99%